Dithiophene-TTF Salts; New Ladder Structures and Spin-Ladder Behavior - Silva, Rafaela A L; Santos, Isabel C; Wright, Jonathan; Coutinho, Joana T; Pereira, Laura C J; Lopes, Elsa B; Rabaça, Sandra; Vidal-Gancedo, José; Rovira, Concepció; Almeida, Manuel; Belo, Dulce (Inorganic chemistry, 2015)
(α-DT-TTF)2[Au(i-mnt)2] and (α-DT-TTF)2[Co(mnt)2] are two new salts of the donor α-dithiophene-tetrathiafulvalene with stable diamagnetic anions, both presenting a ladder structure of the donors organized in paired segregated stacks. The first one is isostructural with previously reported closely related compounds and presents a magnetic spin-ladder behavior with J∥= 83.5 K and J⊥ = 110.3 K as estimated from spin susceptibility data in single crystals. (α-DT-TTF)2[Co(mnt)2] presents a new structural type with a different arrangement of pairs of donor stacks, alternating with stacks of dimerized [Co(mnt)2] anions which are however arranged in an uncorrelated fashion perpendicular to the stacking axis. Due to the strong coupling between the disordered anion chains and the donor chains, this compound does not present a magnetic spin-ladder behavior. The low temperature superstructure of (DT-TTF)2[Cu(mnt)2] below the transition at 235 K, previously known to be associated with a lattice doubling along the stacking axis, was solved by synchrotron radiation diffraction in small single crystals. It is found that this dimerization is due to donor charge localization with the spin carriers being associated with fully oxidized donor species alternating with neutral donors.